Compressive Strength Performance of High-Volume Fly Ash Concrete with CaCO3 Addition - Wibowo, Yosi Noviari; Tatas; Tajunnisa, Yuyun; Mawardi, Amalia Firdaus; Zanah, Miftaqul (Pusat Publikasi Ilmiah, Institut Teknologi Sepuluh Nopember., 2025)
This study investigates the compressive strength performance of High-Volume Fly Ash (HVFA) concrete with added CaCO3 as a sustainable alternative to Ordinary Portland Cement (OPC) for infrastructure applications. The experimental research replaces a significant portion of cement with fly ash—a byproduct of coal combustion—aiming to reduce greenhouse gas emissions associated with concrete production. Two HVFA concrete mixtures were developed, substituting 37 percent and 47 percent of cement content with fly ash and adding 3 percent CaCO3 to enhance mechanical properties. Material characterization, including XRF and XRD analysis, confirmed the suitability of fly ash for concrete production based on ASTM C618-19 standards. Aggregate gradation, moisture content, and specific gravity tests were conducted to optimize the mix design. Compressive strength tests were performed at 7, 14, and 28 days, showing that HVFA concrete with 37 percent fly ash substitution achieved higher strength values, reaching 25.92 megapascals at 28 days, compared to the 47 percent mix, which reached 24.68 megapascals. Slump tests indicated sufficient workability, with a measured slump of 10 centimeters for FA37C3 and 12 centimeters for FA47C3. These findings suggest that HVFA concrete with moderate fly ash substitution, complemented by CaCO3 addition, can achieve compressive strength and workability comparable to OPC, supporting the development of environmentally friendly concrete solutions.